The Influence of Work Environment, Work Load, Job Stress, and Work Morate on Employee Performance Batam City Notary & PPAT Office - Purwaningrum, Ajeng Handayani; Tanjung, Rona; Tibrani, Tibrani; Melisa, Melisa; Mulyati, Sri (International Conference on Business Management and Accounting, 2023)
This study aims to determine the effect of work environment, workload, work stress and work morale on employee performance at the Notary & PPAT Office of Batam City (Case Study of Notary & PPAT Employee Performance Vivin, S. H., M. Kn and Notary & PPAT Office Yondri Darto, S.H). The type of research used in this research is quantitative research. The population of this study were 41 people who were employees of the Notary & PPAT Office of Vivin, S. H., M. Kn and the Notary & PPAT Yondri Darto, S. H. The sampling technique in this study used a saturated sample technique so that the sample numbered 41 respondents. Data is obtained by distributing questionnaires or questionnaires that have been tested for validity and reliability. Data analysis used multiple linear regression and hypothesis testing using the t test and F test. The data were processed using SPSS version 26. The results of the study were that partially the variables Work Environment, Workload, Work Stress and Work Morale had a significant and significant effect on Employee Performance, and in a significant way Simultaneous Work Environment, Workload, Work Stress, and Work Morale have a significant and significant effect on the Performance of Notary & PPAT Office Employees Vivin, S. H., M. Kn and Notary & PPAT Office Yondri Darto, S. H.